2010
DOI: 10.1143/apex.3.026201
|View full text |Cite
|
Sign up to set email alerts
|

NH3Plasma Pretreatment of 4H-SiC(000\bar1) Surface for Reduction of Interface States in Metal–Oxide–Semiconductor Devices

Abstract: We have investigated NH3 plasma pretreatment and SiON deposition for the C face of 4H-silicon carbide (4H-SiC) and characterized interface properties. It is revealed that the NH3 plasma pretreatment effectively reduces interface state density and increases field-effect mobility on the C face of 4H-SiC. Both nitrogen and hydrogen passivate interface traps, resulting in improved electron channel mobility. Although the threshold voltage was high due to electron traps in the SiON deposition layer, the nitrided lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
1
7
0
2
Order By: Relevance
“…Since JSC is highly susceptible to surface oxidation, wafer slicing waste contained numerous organic bonds because of the cleaning process. In addition to the described characteristics of the peaks, the effects of Si 2p after N-APPJ treatment were determined using Si–N x (101.48 eV), Si–N 1.33 (102.34 eV), Si–O x (103.58 eV), and N–Si–O (104.35 eV), as shown in Figure e and f, indicating the replacement of organic bonds (−OH) x with the doped N, which is consistent with the results of the N spectra and those of previous studies. ,, Table S1 shows a summarized table of XPS data for all electrodes for N 1s and Si 2p.…”
Section: Resultssupporting
confidence: 88%
“…Since JSC is highly susceptible to surface oxidation, wafer slicing waste contained numerous organic bonds because of the cleaning process. In addition to the described characteristics of the peaks, the effects of Si 2p after N-APPJ treatment were determined using Si–N x (101.48 eV), Si–N 1.33 (102.34 eV), Si–O x (103.58 eV), and N–Si–O (104.35 eV), as shown in Figure e and f, indicating the replacement of organic bonds (−OH) x with the doped N, which is consistent with the results of the N spectra and those of previous studies. ,, Table S1 shows a summarized table of XPS data for all electrodes for N 1s and Si 2p.…”
Section: Resultssupporting
confidence: 88%
“…22 Iwasaki et al revealed that NH 3 plasma pretreatment significantly decreased D it due to the passivation of the interface traps by nitrogen and the termination of dangling bonds by hydrogen. 23 ment not only significantly eliminates near-interface traps in the oxide but also effectively terminates Si dangling bonds. 24 Recently, there has been a process of improving device stability by NO annealing treatment of the SiC surface prior to dielectric deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the existence of initial surface defects (i.e., dangling bonds, C- or O-contaminants and adsorbates, C-related point defects) is also one of the main reasons for the poor quality of the SiC/SiO 2 interface. Several publications have reported the methods to improve the SiC surface characteristics, involving hydrogen/nitrogen plasma treatment, , direct atomic source nitridation treatment, and ultraviolet ozone treatment . Iwasaki et al revealed that NH 3 plasma pretreatment significantly decreased D it due to the passivation of the interface traps by nitrogen and the termination of dangling bonds by hydrogen . Nakashima et al demonstrated that the nitrogen electron cyclotron resonance (ECR) plasma pretreatment not only significantly eliminates near-interface traps in the oxide but also effectively terminates Si dangling bonds .…”
Section: Introductionmentioning
confidence: 99%
“…В настоящей работе используются первый и третий подходы. В качестве адсорбатов рассмотрены N 2 и NH 3 и атомы N. Отметим, что проблема взаимодействия газов N 2 и NH 3 с поверхностью SiC возникла в связи с изучением интерфейса SiO 2 /SiC [13][14][15][16][17]. При этом имеет место диссоциация молекул.…”
Section: Introductionunclassified
“…Найти какие-либо работы непосредственно по адсорбции N 2 , N и NH 3 на SiC не удалось. Поэтому ниже мы будем основываться на косвенных данных и некоторых предположениях, так как экстраполировать на случай поверхности результаты работ [13][14][15][16][17], полученные для объема, не корректно.…”
Section: Introductionunclassified